It's a match! - Entwicklung eines Ansatzes zur Identifikation von Cross-Listings auf Airbnb und TripAdvisor - Wegener, Moritz

Do Online Ratings Matter in the Sharing Economy? Analyzing the Impact of Online Ratings on Demand on Airbnb - Gerzen, Gabriele

Möglichkeiten und Grenzen crowdbasierter Ideenbewertung - Ein systematischer Literaturüberblick - Resch, Tim

Externe Stimuli zur Geschäftsmodell-Ideengenerierung: Ein Experimenteller Ansatz - Milder, Christoph

Blätterwald zur Positionierung in akademischen Texten - Karsten, Andrea (Praxishandbuch Schreibdidaktik. Übungen zur Vermittlung wissenschaftlicher Schreibkompetenzen)

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)
RbInSe2 is attracting growing interest as a secondary semiconductor compound in Cu(In,Ga)Se2-based solar cells by virtue of the recent investigations on absorber post-deposition treatments with alkali metal salts that have resulted in significant efficiency improvements. However, the detection of the RbInSe2 phase on the surface of chalcopyrite absorbers is very challenging due to its nanometric thickness and the limited information available about its fundamental properties. In this context, this work expounds a detailed analysis of the vibrational properties of RbInSe2 that combines first-principle calculations with multiwavelength Raman scattering spectroscopy and provides a methodology for the detection and identification of very thin layers of this material employing solely optical measurements. As a result, here, we present the classification of the different vibrational modes together with the fingerprint Raman spectra of RbInSe2 thin films measured under five different excitations (close to and far from resonance). The employment of a 442 nm excitation wavelength is found to be the most adequate strategy for the detection and characterization of the RbInSe2 phase in view of its resonance with the band gap of the material and its low penetration depth. Additionally, the purity of the deposited thin films as well as the possible influence of the subjacent layers on the Raman spectra of the compound are also investigated by analyzing the presence of secondary phases and by measuring RbInSe2 thin films deposited onto Mo-coated soda-lime glass, respectively. These results set the basis for the future evaluation of the suitability of Raman spectroscopy as a fast and nondestructive characterization technique for the reliable identification and characterization of the nanometric layers of RbInSe2 in Cu(In,Ga)Se2-based solar cells.

Diffusion of Alkali Metals in Polycrystalline CuInSe2 and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas D.; Mirhosseini, Hossein (ACS Applied Materials & Interfaces)
The behavior of alkali atom point defects in polycrystalline CuInSe2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.

Diffusion of Alkali Metals in Polycrystalline CuInSe2 and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas; Mirhosseini, S. Hossein (ACS Applied Materials & Interfaces)
The behavior of alkali atom point defects in polycrystalline CuInSe2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.

Alkali Atoms Diffusion Mechanism in CuInSe 2 Explained by Kinetic Monte Carlo Simulations - Kormath Madam Raghupathy, Ramya; Kühne, Thomas; Henkelman, Graeme; Mirhosseini, Hossein (Advanced Theory and Simulations)
Adaptive kinetic Monte Carlo simulation (aKMC) is employed to study the dynamics and the diffusion of point defects in the CuInSe2 lattice. The aKMC results show that lighter alkali atoms can diffuse into the CuInSe2 grains, whereas the diffusion of heavier alkali atoms is limited to the Cu-poor region of the absorber. The key difference between the diffusion of lighter and heavier alkali elements is the energy barrier of the ion exchange between alkali interstitial atoms and Cu. For lighter alkali atoms like Na, the interstitial diffusion and the ion-exchange mechanism have comparable energy barriers. Therefore, Na interstitial atoms can diffuse into the grains and replace Cu atoms in the CuInSe2 lattice. In contrast to Na, the ion-exchange mechanism occurs spontaneously for heavier alkali atoms like Rb and the further diffusion of these atoms depends on the availability of Cu vacancies. The outdiffusion of alkali substitutional atoms from the grains results in the formation of Cu vacancies which in turn increases the hole concentration in the absorber. In this respect, Na is more efficient than Rb due to the higher concentration of Na substitutional defects in the CuInSe2 grains.

Understanding Artificial Intelligence – A Project for the Development of Comprehensive Teaching Material - Schlichtig, Michael; Opel, Simone Anna; Budde, Lea; Schulte, Carsten (ISSEP 2019 - 12th International conference on informatics in schools: Situation, evaluation and perspectives, Local Proceedings)
Artificial intelligence (AI) has the potential for far-reaching – in our opinion – irreversible changes. They range from effects on the individual and society to new societal and social issues. The question arises as to how students can learn the basic functioning of AI systems, what areas of life and society are affected by these and – most important – how their own lives are affected by these changes. Therefore, we are developing and evaluating school materials for the German ”Science Year AI”. It can be used for students of all school types from the seventh grade upwards and will be distributed to about 2000 schools in autumn with the support of the Federal Ministry of Education and Research. The material deals with the following aspects of AI: Discussing everyday experiences with AI, how does machine learning work, historical development of AI concepts, difference between man and machine, future distribution of roles between man and machine, in which AI world do we want to live and how much AI would we like to have in our lives. Through an accompanying evaluation, high quality of the technical content and didactic preparation is achieved in order to guarantee the long-term applicability in the teaching context in the different age groups and school types. In this paper, we describe the current state of the material development, the challenges arising, and the results of tests with different classes to date. We also present first ideas for evaluating the results.
Keywords: Artificial Intelligence; Machine Learning; Teaching Material; Societal Aspects; Ethics. Social Aspects; Science Year; Simulation Game

Entwicklung und Reflexion einer Unterrichtssequenz zum Maschinellen Lernen als Aspekt von Data Science in der Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael; Schulte, Carsten; Biehler, Rolf; Frischemeier, Daniel; Podworny, Susanne; Wassong, Thomas (INFOS)

Maschinelles Lernen im Unterricht mit Jupyter Notebook - Schlichtig, Michael; Opel, Simone Anna; Schulte, Carsten; Biehler, Rolf; Frischemeier, Daniel; Podworny, Susanne; Wassong, Thomas (INFOS)

Developing Teaching Materials on Artificial Intelligence by Using a Simulation Game (Work in Progress) - Opel, Simone Anna; Schlichtig, Michael; Schulte, Carsten (WiPSCE)

Daniel Napp: Das schlaue Buch vom Büchermachen - Tönsing, Johanna (Grundschulunterricht Deutsch 3 (2019))

Optimization with constraints considering polymorphic uncertainties - Mäck, Markus; Caylak, Ismail; Edler, Philipp; Freitag, Steffen; Hanss, Michael; Mahnken, Rolf; Meschke, Günther; Penner, Eduard (GAMM-Mitteilungen)

Light‐Responsive Serinol‐Based Polyurethane Nanocarrier for Controlled Drug Release - Sun, Jingjiang; Rust, Tarik; Kuckling, Dirk (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Synthesis and characterization of light-degradable bromocoumarin functionalized polycarbonates - Müller, Ann-Kathrin; Jung, Dimitri; Sun, Jingjiang; Kuckling, Dirk (Polymer Chemistry)
The preparation, characterization and degradation properties of novel light-degradable bromocoumarin functionalized polycarbonates were investigated in the present work.

Körper, Macht und Raum. Begehrensstrukturen in der mittelalterlichen Kleinepik (=Diss. masch.). [derzeit in Überarbeitung für den Druck] - Musiol, Marie-Luise

Raum und Figur. Effekte erzählerischer Arrangements in der 'Frauentreue' - Musiol, Marie-Luise (Prägnantes Erzählen (Brevitas 1 – BmE Sonderheft), (online: https://ojs.uni-oldenburg.de/ojs/index.php/bme/issue/view/7))

Die gestohlene Geschichte - Hagengruber, Ruth (philosophie Magazin)
Die Philosophiegeschichte, die heute gelehrt wird präsentiert sich als ein Kanon, der von "großen Männern" dominiert wird. Doch das ist nicht richtig und vor allem, es war nicht immer so. Es gab großartige und einflussreiche Denkerinnen, von Hildegard von Bingen bis Hannah Arendt und Edith Stein, "in allen Ländern und zu allen Zeiten", wie der aufgeklärte Historiograph Jakob Brucker 1745 in seiner Philosophiegeschichte schrieb.
Keywords: women philosophers; stolen history; Ruth Hagengruber

Efficient parallel branch-and-bound search on FPGAs using work stealing and instance-specific designs - Riebler, Heinrich

Karen-Susan Fessel. Bielefelder Poet in Residence 2018 / Paderborner Kinderliteraturtage 2019

Frauen aus der Mitte Deutschlands - Hagengruber, Ruth Edith (Konsens)
Keywords: Interview; Europe; Women; Diversity

Women Philosophers in Early Modern Philosophy - Hagengruber, Ruth Edith (British Journal for the History of Philosophy. Vol. 27)

Enhancement of the local asymmetry in the hydrogen bond network of liquid water by an ultrafast electric field pulse - Elgabarty, Hossam; Kaliannan, Naveen Kaliannan; Kühne, Thomas (Scientific Reports)
Keywords: Multidisciplinary

Kinderideen für Bücher und fürs Leben. Paderborner Grundschulkinder werden auf die Begegnung mit Karen-Susan Fessel vorbereitet - Kruse, Iris (Bielefelder Poet in Residence 2018 / Paderborner Kinderliteraturtage 2019)

Trivialität, Komplexität, Intermedialität - Praxistheoretische Perspektiven auf Medienverbunddidaktik und intermediale Lektüre - Kruse, Iris (Intermedialität. Formen - Diskurse - Didaktik)

Entwicklung einer Methode zur Auslegung von Klebverbindungen in schwingbeanspruchten Konstruktionen des Landmaschinen- und Anlagenbaus (P1121) - Göddecke, Johannes; Meschut, Gerson; Laubrock, Miriam; Göhrs, Tim; Kötting, Gerhard

Nachbildung und Analyse von Schadensmechanismen bei Dichtringen im tribologischen Ersatzsystem - Burkhart, Christoph; Emrich, Stefan; Magyar, Balázs; Kopnarski, Michael; Sauer, Bernd (Tribologie und Schmierungstechnik)
Diese Untersuchung befasst sich mit dem in der Praxis häufig auftretenden, riefenförmigen Verschleiß gehärteter Wellen im Dichtkontakt mit Radialwellendichtringen (RWDR) aus Fluorkautschuk (FKM). Ziel ist es, die Verschleißmechanismen an einer gehärteten Stahlwelle im geschmierten tribologischen Kontakt mit einem elastomeren FKM-Radialwellendichtring anhand experimenteller Modellsysteme aufzuklären. Weiterhin wird die Wechselwirkung des Dichtringverschleißes und Wellenverschleißes aufgrund der sich ständig verändernden Oberflächenmorphologie der Kontaktpartner oberflächenanalytisch charakterisiert. Das entstandene Schadensbild kann simulativ nachgestellt werden und zeigt eine gute Übereinstimmung mit dem tribologischen Experiment.
Keywords: nanoindentation

Efficiency of Worm Gear Drives Under Transient Operating Conditions - Oehler, Manuel; Sauer, Bernd; Magyar, Balázs (Journal of Tribology)
In oil-lubricated worm gears, all moving components cause power losses during operation. These losses depend, among other things, on the viscosity of the lubricant used, which in turn is determined by the temperature present in the gearbox. The dependency between the temperature and the power dissipation is mutual, and they influence each other. For the analysis of gearboxes under transient conditions, the relationship among operating conditions, power dissipation, and temperature must be considered. In this paper, a method for the analysis of these interrelationships is presented, which is based on the combination of tribological simulation and thermal networks. With the developed calculation model, the gearbox efficiency and the temperature over time can be estimated for arbitrary load cases. The calculation results are compared with measurements on a real gearbox.

Kooperation selbst bestimmt? Interdisziplinäre Kooperation und Zielkonflikte in inklusiven Grundschulen und Förderschulen - Neumann, Phillip
Cooperation between teachers and special educators is a central requirement for inclusive schools in which students both with and without special educational needs are taught together. In many studies the autonomy/equity norm is reported as a significant obstacle for cooperation. It implies that teachers strive towards a high amount of autonomy in the sense of ‘privacy in their classroom’ as a reaction to endemic uncertainties of pedagogical work and specific work conditions in schools. Nevertheless, some studies point out that general and special educators strive for and engage in intense forms of cooperation. In this study it is argued from a self-determination theory perspective that cooperation can be accompanied by high values of perceived autonomy if teachers internalized the need for cooperation as part of their professional identity. Furthermore, factors affecting the frequency of cooperation, perception of goal conflict frequency, and stress caused by goal conflicts relating to the endemic uncertainties of pedagogical work are investigated. Analyses were carried out using survey data collected from 222 general and special educators working in either inclusive primary schools, or special schools where pupils had specific special educational needs in the domain of ‘learning’. A key outcome of the study is the absence of the anticipated negative effect of cooperation on the perception of autonomy. This underlines doubts regarding the relevance of the autonomy/equity norm. In addition to that, having special educators with greater levels of experience, as well as the support of the principal through providing fixed time slots for cooperation are identified as central factors supporting cooperation in inclusive schools. Moreover, increased levels of cooperation were found to reduce the perception of goal conflict frequency and stress relating to goal conflicts for general educators. The results of the study are discussed with regard to theoretical implications,the professionalization of general and special educators and opportunities to enhance cooperation and supportive settings in inclusive schools. Die Kooperation von Lehrkräften und Sonderpädagog_innen stellt eine zentrale Bedingung inklusiver Beschulung von Schüler_innen mit und ohne sonderpädagogische Förderbedarfe dar. Als ein maßgebliches Hemmnis der Zusammenarbeit gilt das Autonomie-Paritäts-Muster. Dieses besagt, dass Lehrkräfte aufgrund spezifischer Arbeitsbedingungen und Strukturmerkmale pädagogischer Arbeit in Schule und Unterricht ein hohes Ausmaß an Autonomie i.S.v. ‚Privatheit im Unterricht‘ anstreben. Dennoch weisen Studien darauf hin, dass Lehrkräfte und Sonderpädagog_innen dennoch intensive Kooperationsformen praktizieren und anstreben. In der Arbeit wird mit einem Rückgriff auf die Selbstbestimmungstheorie argumentiert, dass Kooperation auch mit einem hohen Autonomieerleben einhergehen kann, wenn Lehrkräfte und Sonderpädagog_innen Kooperation als Teil ihrer eigenen Professionalität internalisiert haben. Zudem werden Einflussfaktoren auf die Häufigkeit von Kooperation sowie die Wahrnehmung und Belastung von Antinomien und Zielkonflikten als Strukturmerkmale des pädagogischen Handelns untersucht. Grundlage der quantitativ-empirischen Analysen ist eine Stichprobe von insgesamt 222 Lehrkräften und Sonderpädagog_innen in inklusiven Grundschulen und Förderschulen für den Förderschwerpunkt Lernen. Als ein wesentliches Ergebnis der Arbeit zeigt sich, dass negative Effekte der Kooperation auf das Autonomieerleben ausbleiben, sodass die aufgeworfenen Zweifel an der Relevanz des Autonomie-Paritäts-Musters bestärkt werden. Darüber hinaus erweisen sich die Berufserfahrung sowie der Rückhalt der Schulleitung durch geschaffene Zeitfenster im Stundenplan als relevante Einflussfaktoren auf die Häufigkeit der Kooperation von Sonderpädagog_innen in inklusiven Grundschulen. Lehrkräfte in inklusiven Grundschulen nehmen weniger Zielkonflikte und Antinomien wahr und erleben diese weniger belastend, je häufiger sie mit Sonderpädagog_innen kooperieren. Die Ergebnisse werden hinsichtlich theoretischer Implikationen, der Professionalisierung von Lehrkräften und Sonderpädagog_innen sowie Möglichkeiten der Förderung von Kooperation und kooperativer Strukturen diskutiert.
Keywords: Kooperation; Inklusion; Sonderpädagogik; Schulentwicklung; BiLieF

Inklusion im Bremer Schulsystem - Idel, Till-Sebastian; Lütje-Klose, Birgit; Grüter, Sandra; Mettin, Carlotta; Meyer, Andrea; Neumann, Phillip; Büttner, Gerhard; Hasselhorn, Marcus; Schneider, Wolfgang (Zweigliedrigkeit und Inklusion im empirischen Fokus. Ergebnisse der Evaluation der Bremer Schulreform)

Mittendrin oder nur dabei? Sonderpädagogischer Förderbedarf und soziale Partizipation - Neumann, Phillip (SCHULE inklusiv)
Keywords: Soziale Partizipation; Inklusion; Sonderpädagogik; Grundschule

Global generalized solutions to a parabolic-elliptic Keller-Segel system with singular sensitivity - Black, Tobias (Discrete & Continuous Dynamical Systems - S)
Keywords: Applied Mathematics; Discrete Mathematics and Combinatorics; Analysis

The Stokes Limit in a Three-Dimensional Chemotaxis-Navier–Stokes System - Black, Tobias (Journal of Mathematical Fluid Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Condensed Matter Physics; Mathematical Physics

A Keller‐Segel‐fluid system with singular sensitivity: Generalized solutions - Black, Tobias; Lankeit, Johannes; Mizukami, Masaaki (Mathematical Methods in the Applied Sciences)
Keywords: General Engineering; General Mathematics

Stabilization in the Keller–Segel system with signal-dependent sensitivity - Black, Tobias; Lankeit, Johannes; Mizukami, Masaaki (Applicable Analysis)
Keywords: Applied Mathematics; Analysis

Émilie Du Châtelet zwischen Leibniz und Kant. Du Châtelet in der Eberhard-Kant-Kontroverse - Hagengruber, Ruth Edith (Emilie Du Châtelet und die deutsche Aufklärung)
In seiner Auseinandersetzung mit Immanuel Kant bestreitet Johann August Eberhard Kants Anspruch, in seiner Transzendentalphilosophie die Reichweite und Grenzen des Verstandes auf neue, zuvor nicht dagewesene Weise definiert zu haben. Eberhard dagegen meint die Prinzipien und Grundbegriffe transzendentalphilosophischer Erkenntniskritik schon aus der Leibniz-Wolffschen Schule ableiten zu können. An einschlägiger Stelle -- im dritten Teil seiner Ausführungen Über den wesentlichen Unterschied der Erkenntnis durch die Sinne und durch den Verstand -- belegt er diese Behauptung mit einem Verweis auf die {\glqq}Definition{\grqq} der Erscheinung in den Institutions physiques der Philosophin und Mathematikerin Du Châtelet.

Introduction - Hagengruber, Ruth Edith; Hutton, Sarah (British Journal for the History of Philosophy)

Primer - Diester, Michel (Filmische Moderne. 60 Fragmente)

Die sprechende Stadt. Stadtumbau in Paderborn um 1600 und in der Gegenwart - Süßmann, Johannes

Einführung - Eybl, Franz M.; Fulda, Daniel; Süßmann, Johannes (Bündnisse. Politische, soziale und intellektuelle Allianzen im Jahrhundert der Aufklärung)

Bündnisse. Politische, soziale und intellektuelle Allianzen im Jahrhundert der Aufklärung

Das Mainufer von Aschaffenburg: Romantische Geschichtsinszenierung und Herrschaftslegitimation - Süßmann, Johannes (Kolossale Miniaturen. Festschrift für Gerrit Walther)
Keywords: Aschaffenburg Ludwig I. König von Bayern Gartenkunst Main Residenzschloß Villen Gärtner; Friedrich von Antikenrezeption Museen Herrschaftslegitimation Bildungsbürger

Blow your Trumpets Gabriel« – Der Heavy Metal und die Frage des Satanismus - Hansen, Christin (Kirchliche Zeitgeschichte)

Vernünftige Deutsche, chaotische Griechen? Stereotype und historisches Lernen - Hansen, Christin; Pleitner, Berit (Geschichte lernen)

Steuermoral in Westdeutschland nach dem Zweiten Weltkrieg. Eine diskursanalytische Rekonstruktion - Schönhärl, Korinna (Leviathan)
Die Klage über mangelnde Steuermoral ist in der aktuellen Medienberichterstattung omnipräsent, aber sie ist nicht neu: Bereits kurz nach dem Zweiten Weltkrieg wurde bemängelt, die Deutschen in den westlichen Besatzungszonen hinterzögen ihre Steuern. Verfiel die westdeutsche Steuermoral schon damals? Wie veränderte sie sich im Zeitraum zwischen 1945 und 1953? Nach einem kurzen Überblick über die Geschichte der interdisziplinären Steuermoralforschung und einigen methodischen Überlegungen, wie Historiker*innen die Entwicklung der Steuermoral qualitativ untersuchen können, wird im vorliegenden Aufsatz der Diskurs um das Steuerzahlen in der Nachkriegszeit analysiert. Durch die Analyse von Zeitungsberichten und Parlamentsdebatten werden drei unterschiedliche, konkurrierende Narrative identifiziert, die geeignet waren, ganz verschiedene »policy windows« zu öffnen. Die historische Untersuchung zeigt, dass Narrative über das (ehrliche) Steuerzahlen immer mit bestimmten politischen Interessen verknüpft sind - und dass sie deshalb auch im aktuellen Diskurs über das (ehrliche) Steuerzahlen sorgfältig analysiert werden sollten.
Keywords: Political Science and International Relations; Linguistics and Language; Sociology and Political Science; Language and Linguistics

Socially Responsible Investment in 19th Century Greece: A Case Study of a Swiss Banker - Schönhärl, Korinna (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Altruistically motivated investment has become the subject of economic, psychological and sociological research in recent years. The long tradition of ethical considerations concerning investment behavior has often been mentioned by historians but rarely investigated. This paper presents a case study of the 19th century philhellene banker Jean-Gabriel Eynard, who was philanthropically active in Greece, but also invested part of his capital on the emerging Greek market. Drawing on the methodological approach of the “sociology of morality”, this article examines how Eynard invested in Greece, which norms and values concerning investment behavior he articulated and how far they were comparable with the norms and values of today’s Socially Responsible Investment. What emerges is that the practices and the norms of Socially Responsible and Ethical Investment then and now are remarkably similar, while the “moral background” (G. Abend) has changed considerably in some, but not all points.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science; History; Cultural Studies

The full range of leadership. Welche Zusammenhänge gibt es zwischen Führungsverhalten und schulischen Qualitätsindikatoren? - Bloh, Bea; van Ophyusen, Stefanie (Schulmanagement)

Forschendes Lernen in der Lehrerausbildung – Gestaltung und Erforschung des Praxissemesters - Bloh, Bea; Behrmann, Lars; Homt, Martina; van Ophuysen, Stefanie (Herausforderung Kohärenz: Praxisphasen in der universitären Lehrerbildung. Bildungswissenschaftliche und fachdidaktische Perspektiven)